A study on factors affecting share price behaviour - Abdul Hamid, Zauyah (1992)
The purpose of this study is to examine some of the factors affecting share price behaviour and to check the existence of any relationship between the factors and share price. I am trying to establish whether mere is a relationship between earnings per share, net asset and dividend yield with share prices. Once this is established the best linear model will be ascertained. Effectively, the objective here is to test whether the factors under study has an effect on the share price. The approach used to study the relationship between share price and earnings per share, net asset and dividend yield is by using the Regression Technique. The findings indicate mat there are relationships between factors under study and the share price behaviour. The study shows that earnings per share, net asset and dividend yield are important determinants in the valuation of equity. The linear relationships are also seen in all the five years under study with different determinant in each year. The validity and limitation of the study such as data constraints and methodology limitations are also discussed.